2005
DOI: 10.4314/sinet.v26i2.18213
|View full text |Cite
|
Sign up to set email alerts
|

Frankincense and myrrh resources of Ethiopia: II. Medicinal and industrial uses

Abstract: Oleo-gum resins such as frankincense and myrrh are some of the economically and culturally valuable products obtained from trees and shrubs of the genera Boswellia and Commiphora, respectively. They are important natural plant products used in several industries that include pharmacology, food, flavour, liqueur and beverage, cosmetics, perfumery and others. Moreover, frankincense and myrrh have several local applications in medicinal, hygienic, and insecticide areas that could be developed through research. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 42 publications
(52 reference statements)
2
43
0
Order By: Relevance
“…However, a wide variety of therapeutic uses have also been attributed to frankincense, including the treatment of skin diseases, urinary tract infections, respiratory infections, to aid in wound healing, as well as for digestive and gastrointestinal disorders. 5 Many of these conditions are related to bacterial infections and several studies have reported the growth inhibitory properties of frankincense against panels of pathogens. One study screened B. serrata extracts for the ability to inhibit the growth of an extended panel of microbial pathogens associated with skin infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, a wide variety of therapeutic uses have also been attributed to frankincense, including the treatment of skin diseases, urinary tract infections, respiratory infections, to aid in wound healing, as well as for digestive and gastrointestinal disorders. 5 Many of these conditions are related to bacterial infections and several studies have reported the growth inhibitory properties of frankincense against panels of pathogens. One study screened B. serrata extracts for the ability to inhibit the growth of an extended panel of microbial pathogens associated with skin infections.…”
Section: Introductionmentioning
confidence: 99%
“…Today, at least five tree species belonging to the Boswellia genus and the family Burseraceae are exploited for their oleo-gumresin, called frankincense or olibanum (Tucker 1986;Chikamai 2002). In the Horn of Africa, frankincense has numerous traditional, ceremonial and medicinal uses and is an important commodity on the international market (Coppen 1995a,b;Chikamai 2002;Lemenih & Teketay 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(6). Furanosesquiterpenes, the active compounds in C. myrrh essential oil, possessed a significant antiseptic property, also be the characteristic components of pharmaceutical myrrh [26] [36]. All standard bacteria showed resistant to methanolic and aqueous extracts.…”
Section: Resultsmentioning
confidence: 99%